Anticancer Imidazoacridinone C-1311 is Effective in Androgen-Dependent and Androgen-Independent Prostate Cancer Cells - Magdalena Niemira; Barbara Borowa-Mazgaj; Samuel B. Bader; Adrianna Moszyńska; Marcin Ratajewski; Kaja Karaś; Mirosław Kwaśniewski; Adam Krętowski; Zofia Mazerska; Ester M. Hammond; Anna Skwarska (Biomedicines, 2020)
The androgen receptor (AR) plays a critical role in prostate cancer (PCa) development and metastasis. Thus, blocking AR activity and its downstream signaling constitutes a major strategy for PCa treatment. Here, we report on the potent anti-PCa activity of a small-molecule imidazoacridinone, C-1311. In AR-positive PCa cells, C-1311 was found to inhibit the transcriptional activity of AR, uncovering a novel mechanism that may be relevant for its anticancer effect. Mechanistically, C-1311 decreased the AR binding to the prostate-specific antigen (PSA) promoter, reduced the PSA protein level, and, as shown by transcriptome sequencing, downregulated numerous AR target genes. Importantly, AR-negative PCa cells were also sensitive to C-1311, suggesting a promising efficacy in the androgen-independent PCa sub-type. Irrespective of AR status, C-1311 induced DNA damage, arrested cell cycle progression, and induced apoptosis. RNA sequencing indicated significant differences in the transcriptional response to C-1311 between the PCa cells. Gene ontology analysis showed that in AR-dependent PCa cells, C-1311 mainly affected the DNA damage response pathways. In contrast, in AR-independent PCa cells, C-1311 targeted the cellular metabolism and inhibited the genes regulating glycolysis and gluconeogenesis. Together, these results indicate that C-1311 warrants further development for the treatment of PCa.